An endometrium of type C along with an endometrial thickness of < 8 mm are risk factors for ectopic pregnancy after stimulated cycles with fresh embryo transfer - Ying Zhao; Aizhuang Xu; Dong'e Liu; Nenghui Liu; Yumei Li; Zhongyuan Yao; Fen Tian; Hongying Tang; Yanping Li (BMC, 2023)
Abstract Background The study investigated whether specific ultrasonographically observed endometrial features (including endometrium type and thickness) were linked to ectopic pregnancy after stimulated cycles with fresh embryo transfer. Method Of 6246 pregnancy cycles after fresh embryo transfer, 6076 resulted in intrauterine pregnancy and 170 in ectopic pregnancy. The primary outcome of the study was ectopic pregnancy, with the main variables being endometrium type and endometrial thickness. Univariate and subsequent multiple-stepwise logistic regression analyses were used to identify the risk factors of ectopic pregnancy. Results 1. Compared with patients with an endometrial thickness ≥ 8 mm, the adjusted odds ratio for those with an endometrial thickness < 8 mm was 3.368 (P < 0.001). The adjusted odds ratio for women with a type-C endometrium was 1.897 (P = 0.019) compared with non-type C. 2. A larger dose of gonadotropin used during controlled ovarian hyperstimulation was a protective factor against ectopic pregnancy (P = 0.008). 3. The GnRH antagonist protocol (P = 0.007) was a risk factor for ectopic pregnancy, compared with the use of GnRH agonists. Conclusion (1) An endometrial thickness < 8 mm coupled with a type C endometrium significantly increased the risk of ectopic pregnancy after fresh embryo transfer. (2) A thin endometrial thickness and a type C endometrium could be further related to an abnormal endometrial receptivity/peristaltic wave. (3) Patients at a high risk of ectopic pregnancy should therefore be given special attention, with early diagnosis during the peri-transplantation period may assist in the prevention of ectopic pregnancy.